Outcome and Evaluation of the Patient Thyroidectomy with Hyperthyroidism: A Case-Control Study (Medicine Today, 2023)
Introduction: According to reports, pediatric patients with hypothyroidism have a higher risk of complications following surgery than adults. Specifically, this Study's aimed to evaluate how complete thyroidectomy is in youth (18 years) and adults.Materials and Methods: A retrospective case-control study of all (n=100) complete thyroidectomies was performed on 32 pediatric and 68 adult patients who were consecutive from were compared at the Department of ENT, Head & Neck Surgery, Islami Bank Medical College and multicentral base hospital, Rajshahi, Bangladesh, from July 2018 to June 2021.Results: The average patient age in children was 9.7 years (range 3.4-17.9 years) against 44.9 years (range 18.4-84.2 years) in adults. Compared to adults, surgical procedures on children took an average of (2.18 ± 0.08 hrs.) longer to complete in adults (1.66 ± 0.03 hrs) (p = 0.003). The average weight of a thyroid specimen was 48.0 ± 6.4 grams in adults and 38.6.0 ± 8.9 grams in children (range, 6.6-203 grams; p = 0.34). Children had a higher ratio of thyroid weight to body weight (0.94 ± 0.11 gm/kg) than adults (0.67 ± 0.8 gm/kg; p = 0.05). After surgery, the hyperthyroid condition improved in every patient. There were no operational deaths, recurrences, or long-term hypoparathyroidism.Conclusion: It is clear that the technical difficulties associated with treating Graves' disease surgically in children and adults result in longer operational periods. There was no difference in the chances of long-term consequences, including recurrent laryngeal nerve damage or neck hematoma.Medicine Today 2023 Vol.35(1): 40-43